TOWARDS SOCIETY 5.0 : A PILOT STUDY ON COSTLESS SMART TRANSPORTATION BUSINESS MODEL - Riovan Styx, Roring; Chih How, Bong (International Journal of Business and Society (IJBS), 2022)
The goal of Society 5.0 is to create a human-centric society that solves economic development challenges so that people can enjoy an active, comfortable, and high-quality life. Society 5.0 is a society that thoroughly provides various needs of people, regardless of region, age, sex, language, etc., by supplying all the items and services required for the continuation of the society itself. This paper focuses on our attempt to facilitate transportation technology as one of the drivers to achieve Society 5.0 Sustainable Development Goals (SDGs) through Costless Smart Transportation (CST). Our approach delivered a costless transportation service for the society while still being able to provide profits to the management and business partners. Our implementation tourism, education, retail, culinary, and industrial that also provides business opportunities to other sectors. The implementation of the business model is realized through a webbased administrative system and a mobile app for clients and business partners. Our pilot study has shown that the proposed business model allows all levels of society to participate and benefit from it yet allows the program to be sustainable in the long run.